CORPORATE LOBBYING IN THE EUROPEAN UNION (Вісник: Міжнародні відносини, 2025)
The article examines corporate lobbying within the institutional context of the European Union as one of the key instruments of influence on the decision-making process. It explores the mechanisms of interaction between transnational corporations and EU institutions across all stages of the regulatory cycle – from initial consultations to the final adoption of legislative acts. The analysis includes specific examples of corporate actors’ influence on regulatory policy in the field of new genomic technologies, highlighting the risks of distorting the principles of transparency, accountability, and democratic participation